Design Of Portable Injection Waste Destruction Machine With Sterilization System - Sandy Suryady; Eko Aprianto Nugroho; Abdul Muchlis (International Journal of Science, Technology & Management, 2021)
The Community Health Center (Puskesmas) does not yet have special facilities for treating medical waste such as hospitals. Hospital/Puskesmas waste and waste generated by hospital activities and other supporting activities. Make a machine that destroys waste injection equipment equipped with a knife made of SKD as a plastic syringe destroyer. Design of a syringe crushing machine in the form of needles and syringes, Analyze the von misses stress received by the frame structure of the syringe crusher, Analyze the displacement by the load received by the frame structure of the syringe crusher, Analyze the safety factor of the frame structure of the crusher syringe. Analyzing using solidworks 2016 software, the results obtained are the maximum value of von misses, displacement, and safety of factor from the lower frame of the syringe waste crusher machine. Von misses stress obtained in the analysis using Solidworks 2016 gets a value of 48.54 Mpa in software calculations, while in theoretical calculations it is 48.01 Mpa. The percentage of errors calculated by software and theory is 1%. The displacement obtained in the analysis using Solidworks 2016 software is 0.34 mm in theoretical calculations of 0.35 mm. The percentage of errors calculated by software and theory is 2%. The safety factor obtained in the solidwork analysis gets a value of 4.7 ul (upper limit), while the theoretical calculation is 5.2 ul (upper limit) which means this frame is declared safe when the engine is operating.